Effects of shoe bending stiffness on the coordination variability of lower extremities in alternating jump rope skipping - Lia, J.; Wu, K.; Xu, Z.; Ye, D.; Wang, J.; Suo, B.; Lu, Z.; Zhan, J.; Fu, W. (Sports Biomechanics, 2025)
This study aimed to investigate how different longitudinal bending stiffness (LBS) in jump rope shoes affect the coordination variability of lower extremity segments and athletic performance during alternating jump rope skipping (AJRS). Thirty-two elite male athletes performed 30-s AJRS tasks wearing shoes with LBS measured at 3.1 Nm/rad (no-carbon-fibre-plate jump rope shoes, NS), 5.1 Nm/rad (low-stiffness-carbon-fibre-plate jump rope shoes, LS) and 7.6 Nm/rad (high-stiffness-carbon-fibre-plate jump rope shoes, HS). Motion capture tracked lower extremity kinematics. The HS shoes exhibited a more ground contacts in the first stage (p < 0.05) and a shorter average ground contact time (p < 0.05). The HS exhibited a smaller metatarsophalangeal joint (MTPJ) extension angle during 30-44% of the stance phase (p < 0.05), smaller MARP (mean absolute relative phase) of the MTPJ-ankle segments (p < 0.001) and smaller CRP (continuous relative phase) during 24-45% of the stance phase (p < 0.05). Coordination variability of the MTPJ-ankle segments was negatively correlated with the number of ground contacts during AJRS (p < 0.01, adjust R2 = 0.192). HS could provide enhanced stability by reducing coordination variability and enhance performance during the first stage in ARJS. These findings could provide insights for guiding future research and development in jump rope shoe design.